B lymphocyte stimulator levels in systemic lupus erythematosus: Higher circulating levels in African American patients and increased production after influenza vaccination in patients with low baseline levels - Lauren L. Ritterhouse; Sherry R. Crowe; Timothy B. Niewold; Joan T. Merrill; Virginia Roberts; Amy B. Dedeke; Barbara R. Neas; Linda F. Thompson; Joel M. Guthridge; Judith A. James (2011)
Objective To examine the relationship between circulating B lymphocyte stimulator (BLyS) levels and humoral responses to influenza vaccination in systemic lupus erythematosus (SLE) patients, as well as the effect of vaccination on BLyS levels, and to investigate clinical and serologic features of SLE that are associated with elevated BLyS levels. Methods Clinical history, disease activity measurements, and blood specimens were collected from 60 SLE patients at baseline and after influenza vaccination. Sera were tested for BLyS levels, lupus-associated autoantibodies, serum interferon-α (IFNα) activity, 25-hydroxyvitamin D (25[OH]D), and humoral responses to influenza vaccination. Results Thirty percent of the SLE patients had elevated BLyS levels, with African American patients having higher BLyS levels than white patients (P = 0.006). Baseline BLyS levels in patients were not correlated with humoral responses to influenza vaccination (P = 0.863), and BLyS levels increased postvaccination only in the subset of patients with BLyS levels in the lowest quartile (P = 0.0003). Elevated BLyS levels were associated with increased disease activity, as measured by the SLE Disease Activity Index, physician's global assessment, and Systemic Lupus Activity Measure in white patients (P = 0.035, P = 0.016, and P = 0.018, respectively), but not in African Americans. Elevated BLyS levels were also associated with anti–nuclear RNP (P = 0.0003) and decreased 25(OH)D (P = 0.018). Serum IFNα activity was a significant predictor of elevated BLyS in a multivariate analysis (P = 0.002). Conclusion Our findings indicate that African American patients with SLE have higher BLyS levels regardless of disease activity. Humoral response to influenza vaccination is not correlated with baseline BLyS levels in SLE patients, and only those patients with low baseline BLyS levels demonstrate an increased BLyS response after vaccination.